2017
DOI: 10.1097/gox.0000000000001378
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence Rates Over 20 Years in the Treatment of Malignant Melanoma: Immediate Versus Delayed Reconstruction

Abstract: Background:Wide local excision (WLE) with a safety margin is the standard of treatment for primary head and neck cutaneous malignant melanoma (HNCMM). Studies have demonstrated inconsistency in recurrence rates following immediate versus delayed reconstruction. The objectives of this study were to assess and compare recurrence rates after WLE of HNCMM followed by immediate or delayed reconstruction in determining recurrence-free survival estimates.Methods:A consecutive, retrospective analysis of 451 patients u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…13 For instance, a study performed over a period of 20 years (1994–2014) at the Beth Israel Deaconess Medical Center showed that patients with melanoma have an estimated 41.1% recurrence rate. 14…”
Section: Introductionmentioning
confidence: 99%
“…13 For instance, a study performed over a period of 20 years (1994–2014) at the Beth Israel Deaconess Medical Center showed that patients with melanoma have an estimated 41.1% recurrence rate. 14…”
Section: Introductionmentioning
confidence: 99%
“…Surgical resection is the standard first-line treatment for primary melanoma, often combined with chemotherapy, radiation therapy and, more recently, immunotherapy such as with the use of anti-PD1 monoclonal antibodies [ 2 , 3 ]. However, local recurrence rates remain high (≈40%) [ 4 ] and mortality rates have not improved significantly in the past 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…The reported incidence of positive margins ranged from 6 to 20.9% (►Table 1). 4,[7][8][9][10][11][12][13][14] The average rate of positive margins on wide local excision specimens across all studies was 10.1% (170/1,690). Biopsy modality, multiple biopsies at tumor site prior to wide local excision, ulceration, tumor thickness, locally recurrent tumors, increasing patient age, melanoma in situ (MIS) component, noncompliance with recommended margins, histological regression, and the desmoplastic subtype were identified as risk factors for positive margins in these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple recent studies have made blanket conclusions that immediate reconstruction is "oncologically sound" and "safe" following excision with appropriate margins based on depth for cutaneous melanoma of the head and neck. [2][3][4] The only oncological reason to delay reconstruction is to await final pathological interpretation of the margin status of the definitive excision specimen so that reexcision of positive margins could be performed more precisely without compromising the reconstruction. Excision with appropriate margins based on depth and histological subtype, with or without sentinel lymph node biopsy, remains the most frequently recommended modality of treatment by the National Comprehensive Cancer Network.…”
Section: Discussionmentioning
confidence: 99%